The Metaphor of Disease in Maugham's The Painted Veil - Wu, Qian (Frontiers in Humanities and Social Sciences, 2024)
As a renowned British author, W. Somerset Maugham is known for his bold and unusual works. In The Painted Veil, the vain Kitty holds herself in high regard, flitting between numerous suitors with great satisfaction. However, as she reaches marriageable age, she still fails to find a suitable partner. The dull Walter, aware of her superficiality, persistently pursues her, and they eventually marry and move to Hong Kong. After their marriage, however, Kitty does not treat Walter sincerely and instead engages in an inappropriate relationship with the local official, Charlie. When this infidelity is revealed, the taciturn Walter, filled with rage, threatens to take Kitty to the cholera-infested city of Mei Tan Fu. Disease is an inescapable issue for humanity, permeating every aspect of society and affecting human emotions, joys, sorrows, and relationships. Cholera holds significant metaphorical meaning in The Painted Veil. As Susan Sontag discusses in her book "Illness as Metaphor," disease is often associated with death, despair, filth, chaos, and indulgence. In this context, cholera symbolizes the punishment for Kitty's indulgence and her affair, as well as Walter's deliberate revenge and desire to put his wife in danger. The cholera outbreak complicates their emotions and witnesses their growth and transformation.